Empirical Evidence on the Long-Run Money Demand Function in the GCC Countries - Hamdi, Helmi; Said, Ali; Sbia, Rashid (International Journal of Economics and Financial Issues, 2015)
The broad aim of this paper is to estimate the money demand function for the case of six Gulf Cooperation Council countries. By applying panel cointegration tests, the empirical results reveal strong evidence of cointegration between the variables of the model for individual countries as well as for the panel. Moreover, the results support the existence of a stable money function in the long-run estimation. The Granger non-causality test due to Toda and Yamamoto (1995) procedure shows evidence of a bidirectional causal relationship between money demand and income for panel estimation. At an individual level, the results change from one country to another one. Keywords: Money Demand; GCC, Panel Cointegration; Toda-Yamamoto JEL Classifications: C22; C23; E41; E52; F41